1989
DOI: 10.1177/028418518903000317
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Enhancement of Pathologic Lymph Nodes Demonstrated by Computed Tomography

Abstract: Enlarged mediastinal, retroperitoneal and pelvic lymph nodes are often difficult to differentiate from vascular structures. Contrast medium is therefore used to help to discriminate arteries and veins from lymph nodes. This study was undertaken to investigate the degree to which pathologic lymph nodes become enhanced after an intravenous bolus injection of contrast medium. Computed tomography was performed in 25 patients with enlargement of retroperitoneal lymph nodes due to primary lymphoproliferative disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
2
2
0
Order By: Relevance
“…The contrast medium enhancement of LLN of the mediastinum was low or moderate, and the enhancement curves were significantly lower than those of the normal mediastinal lymph nodes. This was in accordance with previous findings in the neck (4, 5) and abdomen (13).…”
Section: Discussionsupporting
confidence: 94%
“…The contrast medium enhancement of LLN of the mediastinum was low or moderate, and the enhancement curves were significantly lower than those of the normal mediastinal lymph nodes. This was in accordance with previous findings in the neck (4, 5) and abdomen (13).…”
Section: Discussionsupporting
confidence: 94%
“…Contrast medium enhancement of LLN of the retroperitoneum was low or moderate, and the enhancement curves were significantly lower than those of the normal retroperitoneal lymph nodes. This study confirmed previous findings in the neck (14, 15), mediastinum (16), and abdomen (27).…”
Section: Discussionsupporting
confidence: 93%
“…Computed tomography of the thorax is commonly used to evaluate the TBLNs for more accurate preoperative staging and surgi- cal planning. [7][8][9][10][11][12] Although CT is widely used in veterinary medicine, the authors believe that its use for the assessment of TBLNs in dogs with primary lung tumors has not been reported. Sensitivities ranging from 25% to 95% and specificities ranging from 46% to 100% have been reported, depending upon the particular study.…”
mentioning
confidence: 99%